Diabetes Mellitus in the Transplanted Kidney - Peev, Vasil; Reiser, Jochen; Alachkar, Nada (Frontiers in Endocrinology, 2014)
Diabetes mellitus (DM) is the most common cause of chronic kidney disease (CKD) and end stage renal disease (ESRD). New onset diabetes mellitus after transplant (NODAT) has been described in approximately 30 percent of non-diabetic kidney transplant recipients many years post transplantation. DM in patients with kidney transplantation constitutes a major comorbidity, and has significant impact on the patients and allografts’ outcome. In addition to the major comorbidity and mortality that result from cardiovascular and other DM complications, long standing DM after kidney transplant has significant pathological injury to the allograft, which results in lowering the allografts and the patients’ survivals. In spite of the cumulative body of data on diabetic nephropathy (DN) in the native kidney, there has been very limited data on the DN in the transplanted kidney. In this review, we will shed the light on the risk factors that lead to the development of NODAT. We will also describe the impact of DM on the transplanted kidney, and the outcome of kidney transplant recipients with NODAT. Additionally, we will present the most acceptable data on management of NODAT.